A bituminous coal-based sodium electric hard carbon negative material and a preparation method thereof
Patent Information
- Application Number
- CN202611187325.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-13
AI Technical Summary
[0002]现有煤基硬碳原料提纯工艺普遍采用盐酸+HF复合强酸酸洗或高浓度NaOH/KOH碱洗脱灰,此类方法易腐蚀碳层界面,并大量损耗烟煤中的内源蛋白与含氧官能团,因此必须通过外源掺氮进行补偿;同时,HF等强酸废水的处理会对环境造成较大压力
本发明烟煤基钠电硬碳负极材料及其制备方法,以新疆低变质弱黏结烟煤为原料制备钠电硬碳负极材料,采用生物酶-有机柠檬酸组合的梯级深度脱灰预处理,大幅降低了HF酸等对环境的危害,并配合低温空气美拉德交联反应锁定内源N/O,无需后期额外包覆外氮源,有效解决了传统外源掺氮仅附着于材料表面、影响首次库伦效率的问题;此外,通过低温盐限域预扩层预先打开碳层间距,再经三段梯度碳化调控材料孔结构,既保证了足够的储钠活性位点以提升可逆容量,又能闭合开放孔道、降低材料比表面积以减少副反应;最后经低温气相钝化处理稳定材料表面界面,进一步提升首次库伦效率与循环稳定性同时,采用三段梯次热处理工艺,结合微量碱扩孔技术与后处理钝化技术,可有效增加储钠空间以提升克容量,同时降低材料比表面积,保障首次效率。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of hard carbon materials for sodium-ion battery anodes, and specifically discloses a bituminous coal-based hard carbon anode material for sodium-ion batteries and its preparation method. Background Technology
[0002] Current purification processes for coal-based hard carbon raw materials generally employ hydrochloric acid + HF composite strong acid washing or high-concentration NaOH / KOH alkaline washing for deashing. These methods easily corrode the carbon layer interface and significantly deplete the endogenous proteins and oxygen-containing functional groups in bituminous coal, thus requiring compensation through exogenous nitrogen doping. Simultaneously, the treatment of strong acid wastewater such as HF places considerable pressure on the environment. Furthermore, traditional hard carbon nitrogen sources are mostly derived from exogenous coatings such as urea, melamine, and ammonia. These exogenous nitrogen sources can only adsorb onto the particle surface, severely impacting the material's initial coulombic efficiency. Summary of the Invention
[0003] To address the problems in the background art, this invention discloses a bituminous coal-based sodium-carbon hard anode material and its preparation method. It employs a step-by-step deep deashing pretreatment using a combination of bio-enzymes and organic citric acid, and locks in the intrinsic N / O through a low-temperature air Maillard crosslinking reaction, eliminating the need for subsequent external nitrogen source coating. Furthermore, it utilizes a three-stage step-by-step heat treatment process, combined with micro-alkali pore-expansion technology and post-treatment passivation technology, which can effectively increase the sodium storage space to improve the specific capacity, while reducing the material's specific surface area and ensuring the initial efficiency.
[0004] To achieve the above-mentioned objectives, the present invention adopts the following technical solution: A method for preparing a bituminous coal-based sodium-carbon hard anode material specifically includes the following steps: Step 1, Crushing and Slurry Preparation: Take raw bituminous coal for coarse crushing, and then prepare the crushed bituminous coal into slurry with a solid content of 42-58 wt.%; Step 2, enzymatic hydrolysis: Add 3.7-19.4% of the bio-enzyme by weight of the prepared bituminous coal slurry, and hydrolyze at a constant temperature of 50-56℃ for 11-17 hours with stirring. Step 3, Organic acid washing: Separate the solid and liquid components of the enzymatically hydrolyzed material, add a citric acid aqueous solution with a concentration of 3.22-9.38 mol / L to the separated material, stir at 49-53℃ for 9-13 hours, and then filter. Step 4, washing and drying: First, wash the material after soaking in Step 3 with pure water until it is neutral, then dry and crush it; Step 5, Maillard crosslinking reaction: Spread the pulverized bituminous coal evenly in a crucible, heat it to 110℃~130℃ with an air flow rate of 1.18L / min and a heating rate of 0.9℃ / min, and crosslink at a constant temperature for 4.5~6.5 hours; Step 6, Mixing: Mix the cross-linked bituminous coal powder and calcium tartrate dry powder at a mass ratio of 1:(0.25~3.0) using low-speed ball milling; Step 7, Carbonization: The bituminous coal powder mixed with calcium tartrate dry powder is subjected to three-stage gradient carbonization in a high-purity nitrogen atmosphere. After carbonization, the material is cooled to room temperature and taken out of the furnace. It is then washed 2-3 times with citric acid solution at room temperature, and then washed with pure water until neutral before drying. Step 8, passivation: The carbonized bituminous coal powder is placed in a tubular furnace and heated to 310℃~350℃ at a rate of 3℃ / min under the condition of high-purity N2 flow rate of 0.5L / min, and passivated at a constant temperature for 1h~2h. After passivation, the material is first cooled to below 75℃ by nitrogen and then discharged. After mixing, sieving, demagnetizing and packaging, the target hard carbon anode material is obtained.
[0005] Furthermore, in the method for preparing the bituminous coal-based sodium-carbon hard anode material, in step one, the primary bituminous coal is low-rank, weakly caking bituminous coal from Xinjiang, and the mass percentage of ash in the bituminous coal is 14-17%.
[0006] Furthermore, in the method for preparing the bituminous coal-based sodium-carbon hard anode material, in step one, the particle size of the crushed bituminous coal is 5-25 mm.
[0007] Furthermore, in the method for preparing the bituminous coal-based sodium-hard carbon anode material, in step two, the bioenzyme is a protease or a neutral protease.
[0008] Furthermore, in the preparation method of the bituminous coal-based sodium-carbon hard anode material, in step four, the material is washed with water until the pH value of the washing solution is 6.6-7.3.
[0009] Furthermore, in the preparation method of the bituminous coal-based sodium-carbon hard anode material, in step four, the material is dried at 105-108℃, the ash content of the material after drying is ≤0.9%, and the dried material is pulverized to 100 mesh using a pulverizer.
[0010] Furthermore, in the preparation method of the bituminous coal-based sodium-carbon hard anode material, step seven involves carbonization using a three-stage gradient temperature curve: stage A is low-temperature pre-carbonization, with the temperature uniformly increased to 440℃~450℃ and held for 2~3 hours; stage B involves uniformly increasing the temperature from 440℃~450℃ to 850℃~900℃ and holding for 2~3 hours; stage C involves uniformly increasing the temperature from 850℃~900℃ to 1200℃~1280℃ and holding for 3~4 hours.
[0011] Furthermore, in the method for preparing the bituminous coal-based sodium-carbon hard anode material, in step seven, the carbonized bituminous coal material is mixed with a 2.5 mol / L citric acid solution at a solid-liquid ratio of 1:4 for cleaning.
[0012] Furthermore, in the method for preparing the bituminous coal-based sodium-carbon hard carbon anode material, step eight specifies the target hard carbon anode material as follows: D50: 5–7 μm, reversible specific capacity: 345–356 mAh / g, initial efficiency: ≥88%, interlayer spacing d002: ≥0.385 nm, and BET: ≤6.0 μm. 2 / g, Finished product ash content: ≤1.0%.
[0013] A bituminous coal-based sodium-carbon hard anode material is prepared using any one of the above-described methods for preparing bituminous coal-based sodium-carbon hard anode materials.
[0014] Compared with the prior art, the beneficial effects of the present invention are: This invention relates to a bituminous coal-based sodium-ion battery hard carbon anode material and its preparation method. The material is prepared using low-rank, weakly bonded bituminous coal from Xinjiang as raw material. A step-by-step deep deashing pretreatment combining bio-enzymes and organic citric acid significantly reduces the environmental hazards of HF acids. Furthermore, a low-temperature air Maillard crosslinking reaction locks in the intrinsic N / O content, eliminating the need for subsequent external nitrogen coating. This effectively solves the problem of traditional exogenous nitrogen doping only adhering to the material surface and affecting initial coulombic efficiency. In addition, a low-temperature salt-confined pre-expansion layer opens the carbon layer spacing, followed by three-stage gradient carbonization to regulate the material's pore structure. This ensures sufficient sodium storage active sites to improve reversible capacity while closing open pores and reducing the material's specific surface area to minimize side reactions. Finally, low-temperature vapor-phase passivation stabilizes the material's surface interface, further improving initial coulombic efficiency and cycle stability. Simultaneously, a three-stage gradient heat treatment process, combined with micro-alkali pore-expanding technology and post-treatment passivation technology, effectively increases the sodium storage space to improve specific capacity while reducing the material's specific surface area and ensuring initial efficiency. Detailed Implementation
[0015] To better understand the present invention, the following embodiments further illustrate the content of the invention, but the scope of protection of the present invention is not limited to the following embodiments. Numerous specific details are set forth in the following description to provide a more thorough understanding of the invention. However, it will be apparent to those skilled in the art that the present invention can be practiced without one or more of these details. Example 1
[0016] A method for preparing a bituminous coal-based sodium-carbon hard anode material specifically includes the following steps: Step 1, Crushing and Slurry Preparation: Take Xinjiang low-rank weakly caking bituminous coal with an ash content of 15.3 wt.% as raw material. First, coarsely crush it through a crusher. After crushing, the particle size of the material is ≤15mm. Then, adjust the crushed bituminous coal into slurry with a solid content of 50 wt.%. Step 2, Enzymatic hydrolysis: Add 10.1% of neutral protease by weight of bituminous coal to the adjusted bituminous coal slurry, and hydrolyze at a constant temperature of 53℃ for 14 hours to preferentially degrade the protein organic matter that encapsulates inorganic ash. Step 3, Organic acid immersion: Separate the solid and liquid components of the enzymatically hydrolyzed material, add a 6.5 mol / L citric acid aqueous solution to the filtered solid material, stir and immerse at 51°C for 11 hours to dissolve the minerals, and then filter. Step 4, Washing and Drying: First, wash the material soaked in Step 3 with room temperature pure water 3 times. The pH value of the washing solution is 6.6. Then, dry it at 105℃ for 12 hours. Then, pulverize it to 100 mesh using a ball mill. After purification, the ash content of the material is reduced to 0.76wt.%, and the moisture content of the material after drying is ≤5.5%. Step 5, Maillard crosslinking reaction: The pulverized bituminous coal is spread evenly in a crucible and heated to 120°C at an air flow rate of 1.18 L / min and a heating rate of 0.9°C / min. The mixture is kept at a constant temperature for 5.5 hours to crosslink the N and O functional groups through covalent crosslinking of endogenous proteins and polysaccharides without the need to add exogenous doping reagents. Step 6, Mixing: Mix the cross-linked bituminous coal powder with calcium tartrate dry powder at a mass ratio of 1:2.5 and ball mill at low speed for 28 minutes. Calcium tartrate is a homologous organic calcium salt that does not contain transition metals and is used for subsequent in-situ generation of nano-CaO confined domains and pre-expansion of carbon layers. Step 7, Carbonization: The bituminous coal powder mixed with calcium tartrate dry powder is placed in a tube furnace and subjected to three-stage gradient carbonization under a high-purity nitrogen atmosphere: Stage A is low-temperature pre-carbonization, with the temperature increased to 440℃ at a rate of 2℃ / min and held at that temperature for 2 hours; Stage B is increased from 440℃ to 860℃ at a rate of 1.3℃ / min and held at that temperature for 2.2 hours; Stage C is increased from 860℃ to 1280℃ at a rate of 0.8℃ / min and held at that temperature for 3.2 hours, and then allowed to cool naturally to room temperature. This gradient carbonization process solidifies a wide carbon layer structure of more than 0.39nm, inhibiting graphitization. After carbonization, the material is cooled to room temperature and removed from the furnace. The carbonized bituminous coal material is mixed with 2.5 mol / L citric acid solution at a solid-liquid ratio of 1:4 and washed twice to dissolve the nano-CaO template inside the material. Then it is washed with pure water until neutral and placed in a vacuum drying oven at 102℃ for 7 hours. Step 8, passivation: The carbonized bituminous coal powder is placed in a tubular furnace and heated to 310°C at a rate of 3°C / min under the condition of high-purity N2 flow rate of 0.5L / min, and passivated at a constant temperature for 1 hour. After passivation, the material is first cooled to below 75°C by nitrogen and then discharged. The passivated hard carbon material is then processed by mixing, sieving, demagnetizing, and packaging in the finished product line to obtain the target sodium-ion battery hard carbon anode material. Example 2
[0017] A method for preparing a bituminous coal-based sodium-carbon hard anode material specifically includes the following steps: Step 1, Crushing and Slurry Preparation: Take Xinjiang low-rank weakly caking bituminous coal with an ash content of 16.5 wt.% as raw material, first crush it through a crusher, and the particle size of the crushed material is ≤15mm. Then, prepare the crushed bituminous coal into slurry with a solid content of 42 wt.%. Step 2, enzymatic hydrolysis: Add 4.0% of the mass of bituminous coal to the adjusted bituminous coal slurry, and stir at a constant temperature of 50°C for 12 hours to preferentially degrade the protein organic matter that encapsulates the inorganic ash. Step 3, Organic acid immersion: Separate the solid and liquid components of the enzymatically hydrolyzed material, add a 4.0 mol / L citric acid aqueous solution to the filtered material, stir and immerse at 51℃ for 10 hours to dissolve the minerals, and then filter. Step 4, Washing and Drying: First, wash the material soaked in Step 3 with room temperature pure water 3 times. The pH value of the washing solution is 6.9. Then, dry it at 105℃ for 12 hours. Then, pulverize it to 100 mesh using a ball mill. After purification, the ash content of the material is reduced to 0.88wt.%, and the moisture content of the dried material is ≤5.5%. Step 5, Maillard crosslinking reaction: The pulverized bituminous coal is spread evenly in a crucible and heated to 112°C at an air flow rate of 1.18 L / min and a heating rate of 0.9°C / min. The mixture is kept at a constant temperature for 6.5 hours to crosslink the N and O functional groups through covalent crosslinking of endogenous proteins and polysaccharides without the need to add exogenous doping reagents. Step 6, Mixing: Mix the cross-linked bituminous coal powder with calcium tartrate dry powder at a mass ratio of 1:0.3 and ball mill at low speed for 28 minutes. Calcium tartrate is a homologous organic calcium salt that does not contain transition metals and is used for subsequent in-situ generation of nano-CaO confined domains and pre-expansion of carbon layers. Step 7, Carbonization: The bituminous coal powder mixed with calcium tartrate dry powder is placed in a tube furnace and subjected to three-stage gradient carbonization under a high-purity nitrogen atmosphere: Stage A is low-temperature pre-carbonization, with the temperature increased to 440℃ at a rate of 2℃ / min and held at that temperature for 2 hours; Stage B is increased from 440℃ to 850℃ at a rate of 2.5℃ / min and held at that temperature for 2.5 hours; Stage C is increased from 850℃ to 1280℃ at a rate of 1.0℃ / min and held at that temperature for 3.5 hours, and then allowed to cool naturally to room temperature. This gradient carbonization process solidifies a wide carbon layer structure of more than 0.39nm, inhibiting graphitization. After carbonization, the material is cooled to room temperature and removed from the furnace. The carbonized bituminous coal material is mixed with a 2.5 mol / L citric acid solution at a solid-liquid ratio of 1:4 and washed twice at room temperature to dissolve the nano-CaO template inside the material. Then it is washed with pure water until neutral and placed in a vacuum drying oven at 102℃ for 7 hours. Step 8, passivation: The carbonized bituminous coal powder is placed in a tubular furnace and heated to 330°C at a rate of 3°C / min under the condition of high-purity N2 flow rate of 0.5L / min, and passivated at a constant temperature for 1.5h. After passivation, the material is first cooled to below 75°C by nitrogen and then discharged. The passivated hard carbon material is then processed by mixing, sieving, demagnetizing, and packaging in the finished product line to obtain the target sodium-ion battery hard carbon anode material. Example 3
[0018] A method for preparing a bituminous coal-based sodium-carbon hard anode material specifically includes the following steps: Step 1, Crushing and Slurry Preparation: Take Xinjiang low-rank weakly caking bituminous coal with an ash content of 14.3 wt.% as raw material, first crush it through a crusher, and the particle size of the crushed material is ≤15mm. Then, prepare the crushed bituminous coal into slurry with a solid content of 58 wt.%. Step 2, enzymatic hydrolysis: Add 17.4% protease by weight of bituminous coal to the adjusted bituminous coal slurry, and hydrolyze at a constant temperature of 56℃ for 16 hours to preferentially degrade the protein organic matter that encapsulates inorganic ash. Step 3, Organic acid immersion: Separate the solid and liquid components of the enzymatically hydrolyzed material, add an 8.5 mol / L citric acid aqueous solution to the filtered material, stir and immerse at 51℃ for 12 hours to dissolve the minerals, and then filter. Step 4, Washing and Drying: First, wash the material soaked in Step 3 with room temperature pure water 3 times. The pH value of the washing solution is 7.0. Then, dry it at 105℃ for 12 hours. Then, pulverize it to 100 mesh using a ball mill. After purification, the ash content of the material is reduced to 0.62wt.%, and the moisture content of the dried material is ≤5.5%. Step 5, Maillard crosslinking reaction: The pulverized bituminous coal is spread evenly in a crucible and heated to 128°C at an air flow rate of 1.18 L / min and a heating rate of 0.9°C / min. The mixture is kept at a constant temperature for 4.5 hours to crosslink the N and O functional groups through covalent crosslinking of endogenous proteins and polysaccharides, without the need to add exogenous doping reagents. Step 6, Mixing: Mix the cross-linked bituminous coal powder with calcium tartrate dry powder at a mass ratio of 1:0.45 and ball mill at low speed for 28 minutes. Calcium tartrate is a homologous organic calcium salt that does not contain transition metals and is used for subsequent in-situ generation of nano-CaO confined domains and pre-expansion of carbon layers. Step 7, Carbonization: The bituminous coal powder mixed with calcium tartrate dry powder is placed in a tube furnace and subjected to three-stage gradient carbonization under a high-purity nitrogen atmosphere: Stage A is low-temperature pre-carbonization, with the temperature increased to 450℃ at a rate of 2℃ / min and held at that temperature for 3 hours; Stage B is increased from 450℃ to 900℃ at a rate of 1.5℃ / min and held at that temperature for 2.5 hours; Stage C is increased from 900℃ to 1250℃ at a rate of 1.0℃ / min and held at that temperature for 3.5 hours, and then allowed to cool naturally to room temperature. This gradient carbonization process solidifies a wide carbon layer structure of more than 0.39nm, inhibiting graphitization. After carbonization, the material is cooled to room temperature and removed from the furnace. The carbonized bituminous coal material is mixed with a 2.5 mol / L citric acid solution at a solid-liquid ratio of 1:4 and washed twice at room temperature to dissolve the nano-CaO template inside the material. Then it is washed with pure water until neutral and placed in a vacuum drying oven at 102℃ for 7 hours. Step 8, Passivation: The carbonized bituminous coal powder is placed in a tubular furnace and heated to 350°C at a rate of 3°C / min under the condition of high-purity N2 flow rate of 0.5L / min, and passivated at a constant temperature for 1 hour. After passivation, the material is first cooled to below 75°C by nitrogen and then discharged. The passivated hard carbon material is then processed by mixing, sieving, demagnetizing, and packaging in the finished product line to obtain the target sodium-ion battery hard carbon anode material. Example 4
[0019] A method for preparing a bituminous coal-based sodium-carbon hard anode material specifically includes the following steps: Step 1, Crushing and Slurry Preparation: Take Xinjiang low-rank weakly caking bituminous coal with an ash content of 15.3 wt.% as raw material. First, coarsely crush it through a crusher. After crushing, the particle size of the material is ≤15mm. Then, adjust the crushed bituminous coal into slurry with a solid content of 50 wt.%. Step 2, enzymatic hydrolysis: Add 10.1 wt.% of neutral protease to the adjusted bituminous coal slurry and hydrolyze it at a constant temperature of 53°C for 14 hours to preferentially degrade the protein organic matter that encapsulates the inorganic ash. Step 3, Organic acid immersion: Separate the solid and liquid components of the enzymatically hydrolyzed material, add an 8.5 mol / L citric acid aqueous solution to the filtered material, stir and immerse at 51°C for 12 hours to dissolve the minerals, and then filter. Step 4, Washing and Drying: First, wash the material soaked in Step 3 with room temperature pure water 3 times. The pH value of the washing solution is 7.0. Then, dry it at 108℃ for 12 hours. Then, pulverize it to 100 mesh using a ball mill. After purification, the ash content of the material is reduced to 0.76wt.%, and the moisture content of the dried material is ≤5.5%. Step 5, Maillard crosslinking reaction: The pulverized bituminous coal is spread evenly in a crucible and heated to 120°C at an air flow rate of 1.18 L / min and a heating rate of 0.9°C / min. The mixture is kept at a constant temperature for 5.5 hours to crosslink the N and O functional groups through covalent crosslinking of endogenous proteins and polysaccharides without the need to add exogenous doping reagents. Step 6, Mixing: Mix the cross-linked bituminous coal powder with calcium tartrate dry powder at a mass ratio of 1:0.35 and ball mill at low speed for 28 minutes. Calcium tartrate is a homologous organic calcium salt that does not contain transition metals and is used for subsequent in-situ generation of nano-CaO confined domains and pre-expansion of carbon layers. Step 7, Carbonization: The bituminous coal powder mixed with calcium tartrate dry powder is placed in a tube furnace and subjected to three-stage gradient carbonization under a high-purity nitrogen atmosphere: Stage A is low-temperature pre-carbonization, with the temperature increased to 450℃ at a rate of 2℃ / min and held at that temperature for 2 hours; Stage B is increased from 450℃ to 850℃ at a rate of 1.5℃ / min and held at that temperature for 2.2 hours; Stage C is increased from 850℃ to 1200℃ at a rate of 1.5℃ / min and held at that temperature for 3.2 hours, and then allowed to cool naturally to room temperature. This gradient carbonization process solidifies a wide carbon layer structure of more than 0.39nm, inhibiting graphitization. After carbonization, the material is cooled to room temperature and removed from the furnace. The carbonized bituminous coal material is mixed with a 2.5 mol / L citric acid solution at a solid-liquid ratio of 1:4 and washed twice at room temperature to dissolve the nano-CaO template inside the material. Then it is washed with pure water until neutral and placed in a vacuum drying oven at 102℃ for 7 hours. Step 8, passivation: The carbonized bituminous coal powder is placed in a tubular furnace and heated to 350°C at a rate of 3°C / min under the condition of high-purity N2 flow rate of 0.5L / min, and passivated at a constant temperature for 2 hours. After passivation, the material is first cooled to below 75°C by nitrogen and then discharged. The passivated hard carbon material is then processed by mixing, sieving, demagnetizing, and packaging in the finished product line to obtain the target sodium-ion battery hard carbon anode material. Example 5
[0020] A method for preparing a bituminous coal-based sodium-carbon hard anode material specifically includes the following steps: Step 1, Crushing and Slurry Preparation: Take Xinjiang low-rank weakly caking bituminous coal with an ash content of 15.3 wt.% as raw material. First, coarsely crush it through a crusher. After crushing, the particle size of the material is ≤15mm. Then, adjust the crushed bituminous coal into slurry with a solid content of 50 wt.%. Step 2, enzymatic hydrolysis: Add 10.1 wt.% of neutral protease to the adjusted bituminous coal slurry and hydrolyze it at a constant temperature of 53°C for 14 hours to preferentially degrade the protein organic matter that encapsulates the inorganic ash. Step 3, Organic acid immersion: Separate the solid and liquid components of the enzymatically hydrolyzed material, add an 8.0 mol / L citric acid aqueous solution to the filtered material, stir at 51°C for 12 hours to dissolve the minerals, and then filter. Step 4, Washing and Drying: First, wash the material soaked in Step 3 with room temperature pure water 3 times. The pH value of the washing solution is 7.2. Then, dry it at 108℃ for 12 hours. Then, pulverize it to 100 mesh using a ball mill. After purification, the ash content of the material is reduced to 0.76wt.%, and the moisture content of the dried material is ≤5.5%. Step 5, Maillard crosslinking reaction: The pulverized bituminous coal is spread evenly in a crucible and heated to 116°C at an air flow rate of 1.18 L / min and a heating rate of 0.9°C / min. The mixture is kept at a constant temperature for 6.5 hours to crosslink the N and O functional groups through covalent crosslinking of endogenous proteins and polysaccharides, without the need to add exogenous doping reagents. Step 6, Mixing: Mix the cross-linked bituminous coal powder with calcium tartrate dry powder at a mass ratio of 1:1.5 and ball mill at low speed for 28 minutes. Calcium tartrate is a homologous organic calcium salt that does not contain transition metals and is used for subsequent in-situ generation of nano-CaO confined domains and pre-expansion of carbon layers. Step 7, Carbonization: The bituminous coal powder mixed with calcium tartrate dry powder is placed in a tube furnace and subjected to three-stage gradient carbonization under a high-purity nitrogen atmosphere: Stage A is low-temperature pre-carbonization, with the temperature increased to 440℃ at a rate of 2℃ / min and held at that temperature for 2 hours; Stage B is increased from 440℃ to 860℃ at a rate of 1.3℃ / min and held at that temperature for 2.2 hours; Stage C is increased from 860℃ to 1280℃ at a rate of 0.8℃ / min and held at that temperature for 3.2 hours, and then allowed to cool naturally to room temperature. This gradient carbonization process solidifies a wide carbon layer structure of more than 0.39nm, inhibiting graphitization. After carbonization, the material is cooled to room temperature and removed from the furnace. The carbonized bituminous coal material is mixed with a 2.5 mol / L citric acid solution at a solid-liquid ratio of 1:4 and washed twice at room temperature to dissolve the nano-CaO template inside the material. Then it is washed with pure water until neutral and placed in a vacuum drying oven at 102℃ for 7 hours. Step 8, passivation: The carbonized bituminous coal powder is placed in a tubular furnace and heated to 310°C at a rate of 3°C / min under the condition of high-purity N2 flow rate of 0.5L / min, and passivated at a constant temperature for 1 hour. After passivation, the material is first cooled to below 75°C by nitrogen and then discharged. The passivated hard carbon material is then processed by mixing, sieving, demagnetizing, and packaging in the finished product line to obtain the target sodium-ion battery hard carbon anode material.
[0021] Comparative Example The same batch of bituminous coal from Xinjiang had an ash content of 15.3%. It was deashed by acid washing with a strong acid mixture of 2 mol / L HCl and 1 mol / L HF. After drying, urea was added as an external source of nitrogen. Coal powder was mixed with KOH and carbon-alkali in a 1:3 dry method and activated and carbonized in one step at 870 °C. After neutralization with concentrated hydrochloric acid and washing with water, the target sodium-ion battery hard carbon anode material was obtained. The comparative preparation method did not involve segmented closed-cell structure or low-temperature nitrogen passivation.
[0022] The target sodium-ion battery hard carbon anode materials prepared in Examples 1-5 and the comparative examples were used respectively. The particle size, BET specific surface area, interlayer spacing d002, ash content and button cell performance of the hard carbon anode materials were tested. Anode slurries were prepared according to the mass ratio of hard carbon anode material:SP conductive agent:PVDF binder = 91:2:7. The slurries were uniformly coated using a manual I-beam coater and then dried in a forced-air drying oven at 100°C for more than 4 hours. The anode sheets were compacted using a roller press to control the compaction density to 0.7 g / cc, and then processed into small round sheets with a diameter of 12 mm. The button cell casing, separator and the anode sheets were all placed in a 60°C oven to dry for 30 minutes. Then the button cell assembly was completed in a glove box. Finally, the performance was tested under 0.1C charge / 0.1C discharge conditions. The specific test results are listed in Table 1.
[0023] Table 1. Performance of hard carbon anode materials and their prepared button cells in Examples 1-5 and comparative examples.
[0024] Based on the data in Table 1, it can be seen that the reversible specific capacity, first efficiency, 100-cycle reversible capacity retention rate, and powder conductivity of the button cells in Examples 1-5 are all greater than those of the comparative button cells. The ash content of the button cells in Examples 1-5 is lower than that of the comparative button cells. However, the interlayer spacing and powder compaction density of the button cells in Examples 1-5 are comparable to or slightly higher than those of the comparative button cells. Among them, Example 2 has a slightly lower reversible specific capacity and first coulombic efficiency due to its lower interlayer spacing. The first coulombic efficiency is referred to as first efficiency in Table 1. Although Example 3 has the highest reversible specific capacity, the interlayer spacing exceeds 0.4 nm, which also causes a decrease in powder compaction density, cycle performance, and conductivity. The ash content of Examples 4 and 5 is higher than that of Example 1, and their specific capacity and first coulombic efficiency are also relatively lower. Overall, Example 1 has the best performance.
[0025] Unless otherwise specified in the examples, the conditions shall be performed in accordance with conventional conditions or the conditions recommended by the manufacturer; if the manufacturers of the reagents or instruments used are not specified, they are all conventional products that can be purchased through commercial channels.
[0026] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Any other modifications or equivalent substitutions made by those skilled in the art to the technical solutions of the present invention, as long as they do not depart from the spirit and scope of the technical solutions of the present invention, should be covered within the scope of the claims of the present invention.
Claims
1. A method for preparing a bituminous coal-based sodium-carbon hard anode material, characterized in that, Specifically, the following steps are included: Step 1, Crushing and Slurry Preparation: Take raw bituminous coal for coarse crushing, and then prepare the crushed bituminous coal into slurry with a solid content of 42-58 wt.%; Step 2, enzymatic hydrolysis: Add 3.7-19.4 wt.% of biological enzyme (dry basis) to the adjusted bituminous coal slurry and hydrolyze it at a constant temperature of 50-56℃ for 11-17 hours with stirring. Step 3, Organic acid washing: Separate the solid and liquid components of the enzymatically hydrolyzed material, add 3.22-9.38 mol / L citric acid aqueous solution to the separated material, stir at 49-53℃ for 9-13 hours, and filter. Step 4, washing and drying: First, wash the material after soaking in Step 3 with pure water until it is neutral, then dry and crush it; Step 5, Maillard crosslinking reaction: Spread the pulverized bituminous coal evenly in a crucible, heat it to 110-130℃ with an air flow rate of 1.18L / min and a heating rate of 0.9℃ / min, and crosslink at a constant temperature for 4.5-6.5 hours; Step 6, Mixing: Mix the cross-linked bituminous coal powder and calcium tartrate dry powder at a mass ratio of 1:(0.25~3.0) using low-speed ball milling; Step 7, Carbonization: The bituminous coal powder mixed with calcium tartrate dry powder is subjected to three-stage gradient carbonization in a high-purity nitrogen atmosphere. After carbonization, the material is cooled to room temperature and taken out of the furnace. It is then washed 2-3 times with citric acid solution at room temperature, and then washed with pure water until neutral before drying. Step 8, passivation: The carbonized bituminous coal powder is placed in a tubular furnace and heated to 310℃~350℃ at a rate of 3℃ / min under the condition of high-purity N2 flow rate of 0.5L / min, and passivated at a constant temperature for 1h~2h. After passivation, the material is first cooled to below 75℃ by nitrogen and then discharged. After mixing, sieving, demagnetizing and packaging, the target hard carbon anode material is obtained.
2. The method for preparing bituminous coal-based sodium-hard carbon anode material according to claim 1, characterized in that, In step one, the primary bituminous coal is Xinjiang weakly caking long-flame bituminous coal with a coal formation age of Cretaceous period or above, and the mass percentage of ash in the bituminous coal is 14-17%.
3. The method for preparing bituminous coal-based sodium-carbon hard anode material according to claim 1, characterized in that, In step one, the particle size of the coarsely crushed bituminous coal is 5-25 mm.
4. The method for preparing bituminous coal-based sodium-hard carbon anode material according to claim 1, characterized in that, In step two, the biological enzyme is either a protease or a neutral protease.
5. The method for preparing bituminous coal-based sodium-carbon hard anode material according to claim 1, characterized in that, In step four, the material is washed with water until the pH of the washing solution is 6.6 to 7.
3.
6. The method for preparing bituminous coal-based sodium-hard carbon anode material according to claim 1, characterized in that, In step four, the material is dried at 105-108℃, and the ash content of the dried material is ≤0.9%. The dried material is then crushed to 100 mesh using a pulverizer.
7. The method for preparing bituminous coal-based sodium-carbon hard anode material according to claim 1, characterized in that, In step seven, carbonization is carried out using a three-stage gradient temperature curve: stage A is low-temperature pre-carbonization, with the temperature being raised at a constant rate to 440℃~450℃ and held for 2~3 hours; stage B is a uniform temperature rise from 440℃~450℃ to 850℃~900℃ and held for 2~3 hours; stage C is a uniform temperature rise from 850℃~900℃ to 1200℃~1280℃ and held for 3~4 hours.
8. The method for preparing bituminous coal-based sodium-hard carbon anode material according to claim 1, characterized in that, In step seven, the carbonized bituminous coal material is mixed with a 2.5 mol / L citric acid solution at a solid-liquid ratio of 1:4 for cleaning.
9. The method for preparing bituminous coal-based sodium-hard carbon anode material according to claim 1, characterized in that, In step eight, the target hard carbon anode material has the following specifications: D50: 5–7 μm, sodium removal capacity: 345–356 mAh / g, initial efficiency: ≥88%, interlayer spacing d002: ≥0.385 nm, and BET: ≤6.0 μm. 2 / g, Finished product ash content: ≤1.0%.
10. A bituminous coal-based sodium-carbon hard anode material, characterized in that, The material is prepared using the method described in any one of claims 1-9 for preparing bituminous coal-based sodium-hard carbon anode materials.